Association Between Statin Use and Open-angle Glaucoma in Hyperlipidemia Patients: A Taiwanese Population-based Case-control Study. Issue 45 (November 2015) - Chen, Hsin-Yi; Hsu, Sheng-Yao; Chang, Yue-Cune; Lin, Che-Chen; Sung, Fung-Chang; Chen, Wen-Chi; Kao, Chia-Huang
Abstract : Abstract: The aim of the study was to investigate the association between statin use and open-angle glaucoma (OAG) risk in hyperlipidemia patients. We used the research database of the Taiwan National Health Insurance program to conduct a population-based case-control study. A total of 1276 patients with newly diagnosed OAG were identified from 2004 to 2011. Controls comprised of 12, 760 patients without glaucoma and were frequency-matched for age, sex, history of diabetes mellitus, and year of hyperlipidemia diagnosis at a 1:10 ratio. Accumulated defined daily doses (DDDs) of statins prescribed during follow-up were calculated. Average statin use was calculated as the sum of DDDs divided by the duration from the initial statin prescription date to the index date (per year), and was subdivided into 3 levels: <30, 30 to 119, and ≥120 DDDs. Comorbidity, including hypertension, depression, and the Charlson comorbidity index, the frequency of eye care visits, and the use of nonstatin cholesterol-lowering drugs, were all considered as confounding factors. For the group with statin use, the adjusted odds ratio of OAG was 1.02 (95% confidence interval 0.90–1.15) when compared with the group without statin use. Subanalysis showed that a high dosage of statin use (≥120 DDD/y) resulted in a1.24-fold increased risk of OAG (odds ratio 1.24, 95% confidence interval 1.03–1.49). The incidence of OAG was increased with the increase of the dosage of statin use ( P for trend = 0.0458). Clinicians should be cautious of hyperlipidemia patients with a high dosage of statin use because it might be associated with an increased risk of OAG. Ophthalmologist consultation is necessary for this high-risk group.